Analysis of Environmental Sanitation With The Occurrence of Malaria in The Work Area of Sidomulyo Health Center, Gading Cempaka District, Bengkulu City - Taurustya, Hernita (Jurnal Kedokteran Raflesia, 2020)
Background: Malaria is a disease that is re-emerging (transmitted massively) and causes a mortality rate of 10-50% of the total cases of severe malaria that are hospitalized. This disease is transmitted through the bite of the Anopheles mosquito which carries the parasite Plasmodium sp. Bengkulu Province is a malaria endemic area, and malaria cases are evenly found throughout the province every month. This study aims to analyze the relationship of environmental sanitation with malaria in the working area of the Sidomulyo Health Center in Bengkulu City. Method: This study uses a cross sectional research design. The study was conducted in the working area of the Sidomulyo Health Center in Bengkulu City in July 2016. The selection of samples was carried out based on simple random sampling. Primary data collection using questionnaires and secondary data from medical records. Data analysis with chi-square test (x 2) at a significance level of 95% (a0.05). Results: From 82 respondents in this study, there were 50 people with poor environmental sanitation, 9 people were malaria positive and 41 people were negative. While out of 32 people with good sanitation, 14 were malaria positive and 18 were negative. Conclusion: There is a significant relationship between environmental sanitation and malaria in the working area of Sidomulyo Health Center, Gading Cempaka District, Bengkulu City with p = 0.022, c = 0.011. Keywords: Environmental Sanitation, malaria incidence